2021
DOI: 10.1186/s12890-021-01529-z
|View full text |Cite
|
Sign up to set email alerts
|

Asthma prevalence and associated factors among lebanese adults: the first national survey

Abstract: Background No national research has yet explored the prevalence of asthma among adults in Lebanon. This study aims to evaluate the prevalence of physician-diagnosed asthma and current asthma, and their determinants among Lebanese adults 16 years old or above. Methods A cross-sectional study was carried out using a multistage cluster sampling. The questionnaire used collected information on asthma, respiratory symptoms, and risk factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In Lebanon, several studies were conducted on asthmatic patients that tackled the preschool asthma risk factor scale, evaluated association between different factors and both wheezing and asthma development, assessed asthma control, and evaluated the influence of diet and obesity on asthma (20)(21)(22)(23)(24)(25). However, data on patients' QoL is still scarce, particularly among adults (26). Therefore, the purpose of this study is to assess the effect of asthma on physical, emotional, social, and occupational aspects of QoL among Lebanese adult asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…In Lebanon, several studies were conducted on asthmatic patients that tackled the preschool asthma risk factor scale, evaluated association between different factors and both wheezing and asthma development, assessed asthma control, and evaluated the influence of diet and obesity on asthma (20)(21)(22)(23)(24)(25). However, data on patients' QoL is still scarce, particularly among adults (26). Therefore, the purpose of this study is to assess the effect of asthma on physical, emotional, social, and occupational aspects of QoL among Lebanese adult asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…110 These findings confirm earlier meta-analysis from 2014 in children, which found that both F&V intake were inversely associated with wheeze and asthma. 142 Considering the adult population, fruit and/or vegetable intake was inversely associated with asthma risk in some, [143][144][145] but not all studies 10,146,147 In terms of a protective effect on current asthma in cross-sectional studies, high F&V intake was not associated with asthma symptoms, lung function, or asthma exacerbations in one study, 146 though increased fresh fruit intake was related to decreased frequent wheeze and speech limiting attacks in another. 148 In a longitudinal study, however, intake of fruits and tomatoes was associated with a decreased rate of lung function decline, particularly in exsmokers.…”
Section: High Fruit and Vegetable Dietmentioning
confidence: 99%
“…However, the increased presence of side effects that accompany the prolonged use of these medications should be considered [26,48,64]. Inhaled or nebulized SABAs resolve acute asthma symptoms, and their therapeutic effect occurs during the first 15 to 20 min of the first hour of acute asthma, inducing symptomatic relief, but they have no effect on airway inflammation and do not provide a sustained benefit [26,51,57,65]. The inhalation route is considered the most effective method of drug administration for asthmatic patients, because it avoids the effect of the first hepatic step with a minimal reduction in bioavailability and rapid absorption of the drug from the alveolar region to the bloodstream, thus improving the therapeutic efficacy.…”
Section: Anti-asthmatic Medicine In Doses Of 100 250 or 500 Mgmentioning
confidence: 99%